Predictors for development of peripheral arterial disease in pancreas-kidney transplant patients and impact on outcomes - Moreira,Beatriz (2021)
Abstract Introduction: The risk of peripheral arterial disease (PAD) is significantly increased in patients with type 1 diabetes mellitus who have developed chronic kidney disease. Pancreas kidney transplantation seems to be a promising option for these patients as it corrects both dysfunctions. The traditional risk factors for PAD are well defined in the general population. However, in patients undergoing simultaneous pancreas kidney transplant (SPKT) its influence is not well characterized. Objective: The aim of this study was to identify possible risk factors that influence the development and progression of PAD in pancreas-kidney transplanted patients and assess the outcomes of PAD on this population. Methods: We made a retrospective observational study of a group of 229 patients with type I diabetes mellitus and end stage renal disease who underwent pancreas-kidney transplantation. Demographic data, years of diabetes prior to transplant, months of dialysis prior to transplant, smoking, antihypertensive drugs intake, statins intake, cerebrovascular disease, myocardial ischemia, cholesterol levels and serum levels of creatinine, cystatin C, C-reactive protein and albumin were analyzed. Analysis of patients as well as kidney and pancreatic grafts survival was performed. Data were analyzed by SPSS version 27with significance at p < 0.05. Results: Of the total of 216 patients included in the analysis with mean age of 46.01 ± 0.48 years, 32 patients (14,8%) developed symptomatic PAD and 23 patients (10,6%) critical limb ischemia. The major amputation rate in this subgroup was 26,1%. Patients with PAD were characterized by higher levels of LDL-C prior to transplant (p = 0.040), which were associated with a 1.011-fold higher risk of developing the disease. Higher levels of HbA1c 6 months and 3 years after transplant were also present among PAD patients (p = 0.033 and p = 0.022), associated with a respectively 1.512- fold and 1.334-fold higher risk of developing the disease. Patients with PAD had also higher levels of Cystatin C 5 years after transplant (p = 0.015) providing a 2.405-fold higher risk of developing the disease. Additionally, myocardial ischemia was also more prevalent among patients with PAD (p = 0.037) inducing a 3.220-fold higher risk of developing the disease. Survival analysis demonstrated a trend towards lower survival and lower renal graft survival in patients with PAD. Conclusion: Poor metabolic control appears to be associated with the development of symptomatic PAD. Elevated levels of cystatin C were also associated with PAD and this can be an independent marker of progression of disease. Also, this study demonstrated that patients with myocardial ischemia were at higher risk of developing PAD.